Keggin heteropolyacids Mo-based as catalysts in the green and selective oxidation of diphenyl sulfide - Palermo, Valeria (2013)
Heteropolyacids are used as redox catalysts due to their bifunctional properties. Some advantages over conventional catalysts, such as selectivity, easy isolation and reuse, are worth noting. In homogeneous conditions their isolation and recycling can be harder, so thatthey are supported for their use as heterogeneous catalysts. In this work, we compare the catalytic activity of different heteropolyacids with Keggin structure, supported on pure and functionalized silica (with 3-aminopropyltrimethoxysilane). H6PMo11BO40, H6PMo11BiO40, H6PMo11LaO40, and H6PMo11YO40 were synthesized, supported and characterized by several physico chemical techniques. Highly selective results were obtained in the selective oxidation of diphenyl sulﬁde to diphenyl sulfoxide or diphenyl sulfone. Besides, these catalysts can be reused. The above-mentioned reaction is useful due to the importance of these compounds as intermediates in the synthesis of biologically signiﬁcant molecules